(untitled) (Research, Society and Development, 2022)
This study aims to analyze the records of care for cardiorespiratory arrest of the Mobile Emergency Care Service (SAMU) in a municipality in the interior of Paraná. This is a descriptive and exploratory research, of a quantitative nature, carried out with the records of cardiorespiratory arrest care from SAMU in Itaipulândia, Paraná. The data were grouped into several categories: sex, age, month of occurrence, time, outcome. Thus, through this study, higher mortality was observed in the male group, aged between 19 and 86 years, Brazilian nationality. Some individuals have comorbidities, such as hypertension, body mass index above the adequate, diabetes mellitus, cardiovascular and pulmonary diseases. The rate of people without comorbidities or under investigation was low. It was concluded that these factors, associated with cardiorespiratory arrest, had an influence on the mortality of these individuals.